The Anthem companion to Niklas Luhmann - Rogowski, Ralf (Anthem companions to sociology, 2023)
This Companion contains twelve chapters written by proven experts on Luhmann's social systems theory. Among the contributions are overviews of the development of Luhmann's thinking, introductions to key areas of Luhmann's theory of society and critical assessments of core concepts of his social systems theory approach. The chapters cover the main societal function systems of law, politics, the economy, science, religion and art. Among the chapters are assessments of Luhmann's impact on debates on constitutionalism, cultural studies and critical systems theory. There are finally reflections of scholars on the way and importance of Luhmann's thoughts for their thinking and how Luhmann's theory has shaped their work.